2007
DOI: 10.5507/fot.2007.006
|View full text |Cite
|
Sign up to set email alerts
|

The epipelic algae of fishponds of Central and Northern Moravia (The Czech Republic).

Abstract: Epipelic assemblages have not been studied in the Czech Republic yet. The sampling method following Round (1953) was used for the fist time in the Czech Republic. The epipelic assemblages were dominated by diatoms, particularly in mesotrophic and meso-eutrophic fishponds, eutrophic fishponds were dominated by green algae and cyanobacteria. A total of 130 diatom species were found in 16 fishponds, their list with trophic preferences is presented. Seven morphospecies were distinquished within Sellaphora pupula s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 4 publications
2
9
0
Order By: Relevance
“…The study of epipelon was pioneered within freshwater habitats by Round (1953), but epipelic algae in general have received relatively little attention in comparison to studies of phytoplankton (Poulíčková et al, 2008a). Thus, the distribution patterns of benthic algae in fishponds remain largely unexplored (Lysáková et al, 2007;Hašler et al, 2008;Poulíčková et al, 2008a, b).…”
Section: Introductionmentioning
confidence: 97%
“…The study of epipelon was pioneered within freshwater habitats by Round (1953), but epipelic algae in general have received relatively little attention in comparison to studies of phytoplankton (Poulíčková et al, 2008a). Thus, the distribution patterns of benthic algae in fishponds remain largely unexplored (Lysáková et al, 2007;Hašler et al, 2008;Poulíčková et al, 2008a, b).…”
Section: Introductionmentioning
confidence: 97%
“…For example, research on epipelic diatoms from fishponds in Central and Northern Moravia, Czech Republic, showed that 24 h was necessary to trap some larger diatoms, such as Pinnularia and Amphora (Lysa´kova´et al, 2007). In our samples, the epipelic diatoms were Navicula, Frustulia, Pinnularia and Brachysira.…”
Section: Optimum Time To Harvest Motile Diatomsmentioning
confidence: 86%
“…Although leaf litter from surrounding trees contributes to the sediment accumulation, the main source of eutrophication is intensive agriculture in surrounding fields and untreated sewage waters from the village of Bílá Lhota . By contrast to other ponds (LySáková et al 2007) Bílá Lhota has relatively high conductivity. The fishpond is not used for fish production and served as a wastewater recipient until 2004.…”
Section: Methodsmentioning
confidence: 99%